1998
DOI: 10.1007/s002560050459
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of bone scintigraphy and MRI in the early diagnosis of the occult scaphoid waist fracture

Abstract: Six patients (14%) had scaphoid waist fractures. There were other bony injuries in a further six. In 40 patients there was agreement between the BS and MRI findings. In three cases there was discrepancy between the imaging modalities; in all three MRI was found to be the more sensitive and specific. MRI could become the investigation of choice for this injury.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
49
0
3

Year Published

2008
2008
2015
2015

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 95 publications
(52 citation statements)
references
References 11 publications
0
49
0
3
Order By: Relevance
“…The timing of the bone scan relative to the injury ranged from less than 3 days 73 to 19 days. 74 Many studies failed to report the scintigraphy methods, but those that did provide detailed methods reported using 10-20 mCi (750 MBq) of technetium-99 m dimethylene phosphonate and a 3-hour delayed, three-phase bone scan with a pinhole study using a single-headed gamma camera. Three studies assessed the interrater reliability of bone scan.…”
Section: Bone Scanmentioning
confidence: 99%
See 3 more Smart Citations
“…The timing of the bone scan relative to the injury ranged from less than 3 days 73 to 19 days. 74 Many studies failed to report the scintigraphy methods, but those that did provide detailed methods reported using 10-20 mCi (750 MBq) of technetium-99 m dimethylene phosphonate and a 3-hour delayed, three-phase bone scan with a pinhole study using a single-headed gamma camera. Three studies assessed the interrater reliability of bone scan.…”
Section: Bone Scanmentioning
confidence: 99%
“…38,64,72,74,75,88,91,[95][96][97][98][99][100] Investigators reported a variety of criterion standards, including clinical evalua- Figure 12. Ultrasound forest plots.…”
Section: Mrimentioning
confidence: 99%
See 2 more Smart Citations
“…Fowler and colleagues compared bone scanning to MRI for diagnosing occult scaphoid fractures. 20 Of 43 patients, they identified 6 patients with scaphoid fractures and 6 with other types of fractures. Beeres and colleagues evaluated bone scans to identify occult scaphoid fractures.…”
Section: Discussionmentioning
confidence: 99%